Clinical Study of Sintilimab as Second-Line or Above Therapy in Patients With Advanced or Metastatic Gastric Cancer: A Retrospective Study - Nie, Caiyun; Lv, Huifang; Liu, Yingjun; Chen, Beibei; Xu, Weifeng; Wang, Jianzheng; Chen, Xiaobing (Frontiers in Oncology, 2021)
Background: The present study was conducted to analyze the clinical efficacy and safety of sintilimab as second-line or above therapy for patients with advanced or metastatic gastric cancer. Methods: Patients with advanced or metastatic gastric cancer that progressed after prior systemic therapies and treated with sintilimab from March 2019 to July 2020 were retrospectively analyzed in this study. The primary end point was progression free survival (PFS). Secondary end points included objective response rate (ORR), disease control rate (DCR), overall survival (OS) and safety. Results: 52 patients with advanced or metastatic gastric cancer received sintilimab monotherapy or combination therapy after failed from prior systemic therapies. Eight patients achieved partial response (PR), 26 patients had stable disease (SD) and 18 patients had progressive disease (PD). The ORR and DCR were 15.4% (8/52) and 65.4% (34/52), respectively. Median PFS was 2.5 months (95%CI=2.0-3.0) and median OS was 5.8 months (95% CI=4.9-6.7) respectively. The ORR and DCR were 30.0% (6/20) and 80.0% (16/20) in intestinal subtype, which was superior than non-intestinal subtype (ORR: 6.3%, DCR: 56.3%). Patients with intestinal subtype obtained longer PFS (4.0 vs. 1.9) and OS (9.0 vs. 4.1) than non-intestinal subtype. The incidence of grade 3-4 adverse events was 44.2%. Conclusions: Sintilimab monotherapy or combination therapy provide a feasible therapeutic strategy for patients with advanced or metastatic gastric cancer who failed from prior systemic therapies. The efficacy of sintilimab in intestinal subtype was superior than non-intestinal subtype.